A Rare Case of Primary Cutaneous Adenoid Cystic Carcinoma - Ioannis Katsarelas; Afroditi Kotarela; Mattheos Bobos; Alexandra Panagiotou; Periklis Dimasis (Diagnostics)
Primary cutaneous adenoid cystic carcinoma (PCACC) isa rare skin malignancy first reported in the 1970s with limited number of cases found in the literature. These neoplasms are typically identified in middle-to-older-age individuals and are mostly located in the scalp and neck region but can identified throughout the body. We describe the case of a 67-year-old male patient that presented to our department with a slow-growing nodule in the left gluteal region that turned out to be a PCACC and analyze the differential diagnosis, radiology, histopathological findings and successful treatment with a wide local excision. Current literature on the subject is also presented and discussed.